2020
DOI: 10.3389/fnins.2020.586939
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Brain Energy Metabolism: Involvement in Depression and Hypothyroidism

Abstract: Although hypothyroidism appears to be an important factor in the pathogenesis of depression, the impact of thyroid hormones on the bioenergetics of the adult brain is still poorly known. Since metabolic changes are reported to be a key player in the manifestation of depressive disorder, we investigated whether there are differences in selected metabolic markers in the frontal cortex and hippocampus of Wistar Kyoto rats (WKY; an animal model of depression) compared to those of control Wistar rats and whether th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 56 publications
(71 reference statements)
3
18
0
Order By: Relevance
“…The anxiety-like behavior examined in our study with the use of the elevated plus maze test is often observed in addition to depression-like behavior in various animal models of depression, including the WKY rats [ 18 ]. Abnormalities in learning and memory processes in WKY rats have been shown previously in the Morris water maze [ 19 ] and novel object recognition test [ 12 ]. These data are in agreement with our findings that spatial memory impairment, as assayed in the novel object location (NOL) test, also occurred in this rat strain.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…The anxiety-like behavior examined in our study with the use of the elevated plus maze test is often observed in addition to depression-like behavior in various animal models of depression, including the WKY rats [ 18 ]. Abnormalities in learning and memory processes in WKY rats have been shown previously in the Morris water maze [ 19 ] and novel object recognition test [ 12 ]. These data are in agreement with our findings that spatial memory impairment, as assayed in the novel object location (NOL) test, also occurred in this rat strain.…”
Section: Discussionmentioning
confidence: 88%
“…Experimental studies have demonstrated that hypothyroidism impairs learning, short-term and long-term memory, induces changes in neurotransmitters and signaling molecules, and disrupts synaptic plasticity [ 10 , 11 ]. As we have shown in previous studies, thyroid hormone deficiency also leads to metabolic disturbances in the brain both in control animals and in a depression model [ 12 ].…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations